2012
DOI: 10.1371/journal.pone.0041025
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity with Speech Affects Cortical Processing of Auditory Distance Cues and Increases Acuity

Abstract: Several acoustic cues contribute to auditory distance estimation. Nonacoustic cues, including familiarity, may also play a role. We tested participants’ ability to distinguish the distances of acoustically similar sounds that differed in familiarity. Participants were better able to judge the distances of familiar sounds. Electroencephalographic (EEG) recordings collected while participants performed this auditory distance judgment task revealed that several cortical regions responded in different ways dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 36 publications
11
30
0
Order By: Relevance
“…A recent study of auditory distance estimation by humans hearing familiar and foreign speech sounds found that the advantage for forward speech still holds for an unfamiliar foreign language (Wisniewski et al, 2012). Thus, familiarity per se does not seem to be the key factor that makes speech more localizable.…”
Section: Do Mammals Imitate Sounds To Enhance Their Perception Of Actmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of auditory distance estimation by humans hearing familiar and foreign speech sounds found that the advantage for forward speech still holds for an unfamiliar foreign language (Wisniewski et al, 2012). Thus, familiarity per se does not seem to be the key factor that makes speech more localizable.…”
Section: Do Mammals Imitate Sounds To Enhance Their Perception Of Actmentioning
confidence: 99%
“…Familiarity with sound features can dramatically improve an individual's ability to range the source of that sound (Coleman, 1962;Little, Mershon, & Cox, 1992). Humans are also known to be better at ranging speech than artificial sounds (Gardner, 1969), and to be better at ranging forward speech than speech played backward (McGregor, Horn, & Todd, 1985;Wisniewski, Mercado, Gramann, & Makeig, 2012). Because backward speech contains all of the acoustic information present in forward speech, any environmental degradation of sound features associated with propagation will be the same for both forward and backward speech.…”
Section: Do Mammals Imitate Sounds To Enhance Their Perception Of Actmentioning
confidence: 99%
“…Blind individuals discriminate auditory source distance better than normally sighted individuals (Voss et al, 2004 ; Kolarik et al, 2013 ), possibly reflecting learning-induced cortical plasticity in areas normally devoted to vision (e.g., Gougoux et al, 2004 ; Voss et al, 2011 ). Also, the source distance of speech played forward is more accurately judged than the same speech played backwards (McGregor et al, 1985 ; Brungart and Scott, 2001 ; Banks et al, 2007 ; Wisniewski et al, 2012 ). Because the known acoustic cues to distance are well matched between stimuli played forward and time-reversed (McGregor et al, 1985 ; Brungart and Scott, 2001 ), better performance for forward speech suggests that central cognitive processes play a significant role in distance perception.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the distance estimates were the most accurate in the case of live talkers [15,30,40]. It is also noteworthy that in the case of reproduced speech phrases listeners can make relatively accurate estimates to a source playing natural speech but fail when the speech is played backwards [38,41].…”
Section: Auditory Distance Estimationmentioning
confidence: 89%
“…Recently, Wisniewski at al. [41] used open field recordings reproduced in a closed space and reported substantial individual differences among the listeners in judging auditory distance. The differences ranged from 51% to 77%.…”
Section: Individual Differencesmentioning
confidence: 99%